1990
DOI: 10.1128/iai.58.10.3194-3201.1990
|View full text |Cite
|
Sign up to set email alerts
|

Developmental cycle-specific host-free RNA synthesis in Chlamydia spp

Abstract: The incorporation of radiolabeled GTP into RNA in host-free Chiamydia trachomatis serovar L2 organisms was investigated. The incorporation was partially inhibited by rifampin and dactinomycin and hydrolyzed by RNase. RNA made by host-free chlamydiae consisted mainly of species of fewer than 800 bases in size, although 16S and 23S species were noted by agarose-gel electrophoresis. The hybridization of radiolabeled host-free RNA to restriction fragments of the gene encoding the major outer membrane protein was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…These results show that media composition is crucial for the host-free activity of C. trachomatis and that the use of the DGM-21A medium for our host-free incubation experiments was important. This finding should also be kept in mind for the interpretation of some other studies on the host-free activity of RBs and EBs of clinically relevant chlamydiae (Sarov and Becker, 1971;Hackstadt et al, 1985;Hatch, 1988;Crenshaw et al, 1990).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These results show that media composition is crucial for the host-free activity of C. trachomatis and that the use of the DGM-21A medium for our host-free incubation experiments was important. This finding should also be kept in mind for the interpretation of some other studies on the host-free activity of RBs and EBs of clinically relevant chlamydiae (Sarov and Becker, 1971;Hackstadt et al, 1985;Hatch, 1988;Crenshaw et al, 1990).…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, host-free EBs of C. psittaci also did not take up ATP although this organism is an intracellular ATP parasite (Hatch et al, 1982). In contrast, host-free RBs of clinically relevant chlamydiae show a certain spectrum of metabolic activities including lysine uptake, but to the best of our knowledge such activities have only been reported for RBs, which were exposed to extracellular conditions for no longer than 2-4 h (Tamura, 1967;Weiss and Wilson, 1969;Hatch et al, 1982;Crenshaw et al, 1990). However, the strongly time-limited metabolic activity of extracellular RBs and the metabolic inactivity of host-free EBs observed in these studies might only reflect that the incubation medium used was not suitable to sustain the metabolic activity of chlamydial EBs outside of the host.…”
Section: Discussionmentioning
confidence: 98%
“…However, ATP uptake was not detected in EBs (Hatch et al, 1982) although Sarov and Becker reported ribonucleic acid biosynthesis in density gradient purified EBs of C. trachomatis (Sarov & Becker, 1971). Yet while Hatch et al convincingly demonstrated protein, RNA, and DNA synthesis in Chlamydia RBs, they did not detect activity in EBs (Hatch et al, 1985;Hatch, 1988;Plaunt & Hatch, 1988;Crenshaw et al, 1990). Taken together, these findings contributed to the perception of the chlamydial EB as a spore-like metabolically inactive stage, the basis of which was suggested to be related to the highly cross-linked rigid outer membrane that has been proposed to represent a permeability barrier (Bavoil et al, 1984).…”
Section: The Discovery Of Developmental Stage-specific Metabolic Featmentioning
confidence: 97%
“…Chlamydiae are also capable of a¡ecting RNA and DNA [35,58]. Interestingly, RNA and some protein synthesis appears to be developmental cycle stage speci¢c [18,52,73]. It has been observed that when cells are infected with C. psittaci, the rates of synthesis of protein, RNA and DNA in the infected cells never exceed the rates observed with non- [27] (c) Large CRP doublet or EnvB Major structural envelope protein Functional equivalent of peptidoglycan( ?)…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydial growth stops as ATP and reducing power diminish, inducing a decrease of metabolic activities, oxidation of free sulfhydryls into disul¢des (that leads to crosslinking of the cysteine-rich proteins), closing of outer membrane pores, and outer membrane rigidi¢cation as RBs transform to EBs [6,14,75]. In addition, it has been shown that di¡erent proteins are expressed at di¡erent times during the chlamydial cycle [18,36,39,52,73].…”
mentioning
confidence: 99%